2005
DOI: 10.1002/anie.200501740
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anion‐Binding Properties, and In Vitro Anticancer Activity of Prodigiosin Analogues

Abstract: Pro and anti: Recognition of chloride ion and through‐membrane H+/Cl− ion transport (“symport”) could account for the biological effects (anticancer activity) of prodigiosin, as inferred from model studies involving pyrrole‐based anion receptors designed to mimic the key features of this naturally occurring pigment (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(95 citation statements)
references
References 23 publications
1
92
0
Order By: Relevance
“…Indeed, prodigiosin, a tripyrrolic natural product with anticancer properties, represents one of the first described anionophores [10][11][12][13]. It has been reported that its biological activity is partly due to its ability to deacidify acidic compartments within cells, which may cause a drop in pHi, and therefore the onset of apoptosis in cancer cells [9,11,14]. Emulating that characteristic, different anionophores have been designed and evaluated [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prodigiosin, a tripyrrolic natural product with anticancer properties, represents one of the first described anionophores [10][11][12][13]. It has been reported that its biological activity is partly due to its ability to deacidify acidic compartments within cells, which may cause a drop in pHi, and therefore the onset of apoptosis in cancer cells [9,11,14]. Emulating that characteristic, different anionophores have been designed and evaluated [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the positive side, a few systems have been tested in whole cells, epithelia or (in one case) genetically modified mice 14 , using electrophysiological methods such as patch-clamp and Ussing chamber, and shown to induce anion conduction without obvious toxic effects. These anionophores include synthetic 3 peptides conceptually related to natural anion channels 11,[15][16][17] , as well as the steroid-based system 1 from the authors' laboratory 18 , and other small organic molecules 14,19,20 .Less encouragingly, a number of molecules showing anion transport in LUVs have tested positive for anti-cancer cytotoxicity (potentially valuable, but incompatible with CF treatment) 8,[21][22][23][24][25] . Many of these systems, including the well-studied prodigiosin 2 26 , transport protons as well as anions 8,[21][22][23] .…”
mentioning
confidence: 99%
“…Less encouragingly, a number of molecules showing anion transport in LUVs have tested positive for anti-cancer cytotoxicity (potentially valuable, but incompatible with CF treatment) 8,[21][22][23][24][25] . Many of these systems, including the well-studied prodigiosin 2 26 , transport protons as well as anions 8,[21][22][23] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prodigiosin appears to cause apoptosis of cancer cells selectively, 21 and the structural analogue obatoclax is currently in clinical trials for the treatment of cancer. 22 The origin of the biological activity has yet to be unambiguously established, although there is evidence that this class of compound facilitates the co-transport of HCl [23][24][25][26][27][28] and/or the anion exchange of chloride 29,30 across lipid bilayer membranes. Indeed, the antibiotic activity of prodigiosin-like molecules has been related to their activity as transmembrane Cl -carriers.…”
mentioning
confidence: 99%